Estudo comparativo da l-asparaginase de e. Coli e Phaseolus vulgaris utilizando dinâmica molecular - Guimarães, Danilo Vasconcelos (2019)
Acute lymphoid leukemia (ALL) is a disease characterized by affecting lymphocytes, causing an accumulation of abnormal young cells in the bone marrow. Chemotherapy is one of the treatments for this disease and L-asparaginase is one of the drugs used in this treatment. Although several organisms synthesize L-asparaginase, only those of bacterial origin are used as chemotherapeutic. The aim of this work was to study the structural stability of Phaseolus vulgaris L-asparaginase in order to compare its active site with E. coli L-asparaginase to analyze the viability of the plant enzyme as an alternative to bacterial. It was used modeling techniques to obtain the complete structure of P. vulgaris L-asparaginase, Molecular Dynamics (MD) simulation for the structural stability study of the protein and its modeling loops and dockcing to study the interaction of the asparagine substrate with the catalytic site residues present in these loops. The structural stability of the total protein and its loops in water was evaluated, as well as the interactions between the L-asparaginase monomers, in order to identify the determinant residues of stability and that lead to the maintenance of the form and the relation of these determinants with the catalytic sites. The modeling was done by ab initio techniques from the I-TASSER program followed by 100 ns of MD with annealing methodology. The MD simulations used the GROMOS53A6 force field, in aqueous solution and with ions sufficient to maintain the system's 0.15 M concentration, and the trajectory was stored with a total simulation time of 300 ns. The stability of the protein and the loops of both L-asparaginases was analyzed by parameters of mean square deviation and hydrogen bonds. The stability of the quaternary structure is directly influenced by the formation of hydrogen bonds (HBs) between the monomers of the enzyme and the catalytic activity is dependent on these HBs. The prospects are to obtain experimental data on the interaction of the enzyme with its substrate to allow the evaluation of which residues participate actively in the catalysis and to propose point mutations in order to try to increase the specificity of L-asparaginage in order to make it possible as an alternative to L-asparaginase from E. coli.